Perovskite precursor solution, perovskite thin film, photovoltaic device and preparation method

By grinding and drying the perovskite structural material raw materials, the problem of increased water content during the storage of perovskite precursor liquid is solved, production costs are reduced, and the efficiency and stability of perovskite solar cells are improved.

CN119709181APending Publication Date: 2025-03-28TRINA SOLAR CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411969148.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The moisture content of perovskite precursor liquid increases during storage, resulting in a decrease in the crystallization quality of perovskite materials, and the cost of super-dry organic salt raw materials is high, which increases the material cost of film preparation.

Method used

By grinding and drying the perovskite structural material raw materials, dry raw materials are obtained, which reduces the demand for super-dry raw materials, extends the service life of the precursor liquid, and then forms perovskite materials by mixing them with inorganic salts, and removes moisture from the organic salt during vacuum drying.

Benefits of technology

It significantly reduces production costs, improves the efficiency and stability of perovskite solar cells, and extends the service life of the precursor liquid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709181A_ABST
    Figure CN119709181A_ABST
Patent Text Reader

Abstract

The invention belongs to the photovoltaic field, and particularly relates to a perovskite precursor solution, a perovskite thin film, a photovoltaic device and a preparation method. The method for preparing the perovskite precursor solution comprises the following steps: grinding a perovskite structure substance raw material in inert gas, then drying to obtain a dried perovskite structure substance raw material, and dissolving the dried perovskite structure substance raw material in a solvent to obtain the perovskite precursor solution. According to the method, the production cost of the perovskite thin film and the photovoltaic device can be reduced, and the efficiency and the stability of the photovoltaic device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photovoltaics, and in particular relates to a perovskite precursor solution, a perovskite film, a photovoltaic device and a preparation method thereof. Background Art

[0002] Organic-inorganic hybrid perovskite materials have the advantages of high absorption coefficient, adjustable bandgap, long carrier diffusion length, high defect tolerance, simple preparation process, and low material and preparation costs. They are considered to be the new materials closest to commercialization in the photovoltaic market in recent years. After only more than a decade of research, single-junction perovskite solar cells have achieved a high photoelectric conversion efficiency, surpassing the currently commercialized cadmium telluride and copper indium gallium selenide cells, and are very close to the mainstream crystalline silicon (26.7%) solar cells in the market; at the same time, stacked perovskite solar cells have gradually become a hot topic in the world's photovoltaic research field in recent years because of their outstanding advantages such as high efficiency, low cost, and simple preparation process. They are considered to be one of the technologies that are expected to achieve large-scale terrestrial photovoltaic applications.

[0003] Perovskite solar cell technology is gradually moving towards industrialization. In China, many production lines of 100 megawatts have been established, and GW-level production lines are also being prepared. At the same time, the storage time of perovskite precursor solution before preparation and the price of raw materials are becoming more and more concerned. At present, a key reason for the deterioration of perovskite precursor solution is the water content during storage. When the storage time becomes longer, the water content in the perovskite precursor solution increases, and the film crystallization quality of the perovskite material decreases significantly; at the same time, in the preparation process of the perovskite precursor solution, the organic salt raw materials, inorganic salt raw materials and solvents of the perovskite structural materials all contain a certain amount of water, which will all enter the perovskite precursor solution, which seriously affects the film crystallization process of the perovskite material. The cost of removing water from the organic salt raw materials is very high, resulting in extremely high costs for ultra-dry organic salt raw materials, which in turn increases the material cost of perovskite film preparation.

[0004] Therefore, there is an urgent need to develop an ultra-dry perovskite structured material raw material that can reduce production costs and improve the efficiency and stability of photovoltaic devices. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a perovskite precursor solution, a perovskite film, a perovskite solar cell and a preparation method. The present invention grinds the perovskite structure material raw material and then dries it to obtain a dry perovskite structure material raw material, thereby reducing the demand for ultra-dry raw materials, extending the service life of the perovskite precursor solution, significantly reducing the production cost, and improving the efficiency and stability of the perovskite solar cell.

[0006] Specifically, the present invention provides a method for preparing a perovskite precursor solution, the method comprising: grinding a perovskite structural material raw material in an inert gas, and then drying to obtain a dry perovskite structural material raw material, and dissolving the dry perovskite structural material raw material in a solvent to obtain a perovskite precursor solution.

[0007] In one or more embodiments, the raw materials of the perovskite structure material are AX and BX2, A is a monovalent cation, including but not limited to one or more of cesium ion, rubidium ion, methylamine ion, dimethylamine ion, formamidine ion and guanidine ion; B is a divalent cation, including but not limited to one or more of lead ion, copper ion, zinc ion, gallium ion, tin ion and calcium ion; X is a monovalent anion, including but not limited to one or more of iodide ion, bromide ion, chloride ion, fluoride ion, thiocyanate ion, tetrafluoroborate ion and hexafluorophosphate ion.

[0008] In one or more embodiments, the inert gas is nitrogen or argon.

[0009] In one or more embodiments, the grinding time is 1-24 hours.

[0010] In one or more embodiments, the drying is carried out under vacuum conditions, with a vacuum degree of less than 10 -3 Pa;

[0011] In one or more embodiments, the drying temperature is -100-60°C.

[0012] In one or more embodiments, the drying time is 6-48 hours.

[0013] In one or more embodiments, in the perovskite precursor solution, the solvent is selected from one or more of ethanol, isopropanol, methanol, butanol, pentanol, N,N-dimethylformamide, dimethyl sulfoxide, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidinone, acetonitrile, diphenyl sulfoxide and dimethoxyethanol.

[0014] In one or more embodiments, the concentration of B-site ions in the perovskite precursor solution is 0.1-2.4 mol / L.

[0015] The invention provides a perovskite precursor solution prepared by the method described in the invention.

[0016] The invention provides a method for preparing a perovskite film, which comprises: coating the perovskite precursor solution of the invention, and then annealing to obtain the perovskite film.

[0017] In one or more embodiments, the coating method is spin coating, knife coating, spray pyrolysis, inkjet printing or slot coating.

[0018] In one or more embodiments, the annealing temperature is 90-150°C.

[0019] In one or more embodiments, the annealing time is 10-60 min.

[0020] The invention provides a perovskite film prepared by the method described in the invention.

[0021] In one or more embodiments, the perovskite film comprises a perovskite structure material, the chemical formula of the perovskite structure material is ABX3, A is a monovalent cation, including but not limited to one or more of cesium ion, rubidium ion, methylamine ion, dimethylamine ion, formamidine ion and guanidine ion; B is a divalent cation, including but not limited to one or more of lead ion, copper ion, zinc ion, gallium ion, tin ion and calcium ion; X is a monovalent anion, including but not limited to one or more of iodide ion, bromide ion, chloride ion, fluoride ion, thiocyanate ion, tetrafluoroborate ion and hexafluorophosphate ion.

[0022] The present invention provides a photovoltaic device, wherein the photovoltaic device comprises the perovskite film described in the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) is a schematic diagram of the structure of a single-junction perovskite solar cell prepared according to some embodiments of the present invention.

[0024] Figure 1 (b) is a schematic diagram of the structure of a stacked perovskite solar cell prepared according to some embodiments of the present invention. DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0027] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0028] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0029] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0030] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0031] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0032] The present invention provides a method for preparing a perovskite precursor solution, the method comprising: grinding a raw material of a perovskite structure material in an inert gas, then drying, obtaining a dried raw material of a perovskite structure material, dissolving the dried raw material of a perovskite structure material in a solvent, and obtaining a perovskite precursor solution. In the raw material of the perovskite, the water content of the organic salt is relatively high, usually above 200ppm, and the water content of the inorganic salt and the solvent is relatively low, usually below 20ppm after dehydration, so that after being configured into a perovskite solution, the water content in the solution is above 200ppm, and an organic salt such as MAI is easy to volatilize during a vacuum drying process at 60°C, and cannot be further dehydrated, but after the organic salt and the inorganic salt are mixed to form a perovskite material, it will not volatilize during a vacuum drying process at 60°C, so this method can be used to further remove the water contained in the organic salt, thereby reducing the cost of purchasing ultra-dry raw materials, and the perovskite precursor solution with a low water content obtained by adding the perovskite powder after dehydration to the solvent will significantly improve the device performance of the perovskite solar cell.

[0033] In the present invention, the raw materials of the perovskite structure material are AX and BX2, A can be a monovalent cation, including but not limited to cesium ions (Cs + ), rubidium ions (Rb + ), methylamine ion (CH3NH3 + , MA), dimethylamine ion, formamidine ion (CH(NH2)2 + , FA) and guanidine ions; B can be a divalent cation, including but not limited to lead ions (Pb2+ ), copper ions (Cu 2+ ), zinc ion (Zn 2+ ), gallium ions (Ga 2+ ), tin ions (Sn 2+ ) and calcium ions (Ca 2+ ) in one or more; X may be a monovalent anion, including but not limited to iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - ), fluoride ion (F - ), thiocyanate ion (SCN - ), tetrafluoroborate ion (BF4 - ) and hexafluorophosphate ion (PF6 - ). Preferably, the raw material of the perovskite structure material may be one or more selected from lead iodide, lead bromide, lead chloride, cesium iodide, cesium bromide, cesium chloride, rubidium iodide, rubidium bromide, rubidium chloride, iodine methylamine, bromine methylamine, chloromethylamine, iodoformamidine, bromine methylamidine, chloroformamidine, dimethylammonium iodide, dimethylammonium bromide, dimethylammonium chloride, guanidine iodide, guanidine bromide and guanidine chloride.

[0034] In the present invention, the inert gas may be nitrogen or argon. In the present invention, the grinding time may be 1-24 h, for example 2 h, 4 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h.

[0035] In the present invention, drying can be carried out under vacuum conditions, with a vacuum degree of less than 10 -3 Pa;

[0036] In the present invention, the drying temperature can be -100-60°C, for example -100°C, -80°C, -60°C, -40°C, -20°C, 0°C, 20°C, 40°C, 60°C. Organic salts such as MAI are easily volatilized during the vacuum drying process at 60°C and cannot be further dehydrated. However, after the organic salts are mixed with inorganic salts to form perovskite materials, they will not volatilize during the vacuum drying process at 60°C. Therefore, controlling the drying temperature within the above range is beneficial to reduce the volatilization of the raw materials while removing the moisture contained in the organic salts, reducing the cost of purchasing ultra-dry raw materials, and improving the device performance of perovskite solar cells.

[0037] In the present invention, the drying time can be 6-48 hours, for example 6 hours, 12 hours, 18 hours, 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours, 48 ​​hours.

[0038] In the present invention, in the perovskite precursor solution, the solvent can be one or more selected from ethanol, isopropanol, methanol, butanol, pentanol, N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidinone (DMPU), acetonitrile (ACN), diphenyl sulfoxide (DPSO) and dimethoxyethanol.

[0039] In the present invention, the concentration of B-site ions in the perovskite precursor solution may be 0.1-2.4 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.4 mol / L.

[0040] The present invention provides a method for preparing the perovskite film of the present invention, the method comprising: coating a perovskite precursor solution, and then annealing to obtain the perovskite film. In the present invention, the coating method can be spin coating, blade coating, spray pyrolysis, inkjet printing or slit coating.

[0041] In the present invention, the annealing temperature can be 90-150°C, for example 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C; in the present invention, the annealing time can be 10-60min, for example 10min, 20min, 30min, 40min, 50min, 60min.

[0042] In the present invention, the perovskite film may include a perovskite structure material, the chemical formula of the perovskite structure material may be ABX3, A may be a monovalent cation, including but not limited to a cesium ion (Cs + ), rubidium ions (Rb + ), methylamine ion (CH3NH3 + , MA) and formamidinium ion (CH(NH2)2 + , FA) in one or more; B can be a divalent cation, including but not limited to lead ions (Pb 2+ ), copper ions (Cu 2+ ), zinc ion (Zn 2+ ), gallium ions (Ga 2+ ), tin ions (Sn 2+ ) and calcium ions (Ca 2+ ) in one or more; X may be a monovalent anion, including but not limited to iodide ion (I - ), bromide ion (Br - ), chloride ion (Cl - ), fluoride ion (F - ), thiocyanate ion (SCN - ), tetrafluoroborate ion (BF4 -) and hexafluorophosphate ion (PF6 - )

[0043] The present invention provides a photovoltaic device comprising the perovskite film of the present invention. In the present invention, the photovoltaic device may include a single-junction perovskite solar cell or a stacked perovskite solar cell. In the present invention, the photovoltaic device may include a formal perovskite solar cell or an inverted perovskite solar cell.

[0044] In the present invention, the photovoltaic device may include a hole transport layer, a perovskite film and an electron transport layer in sequence. In the present invention, the photovoltaic device may include an electron transport layer, a perovskite film and a hole transport layer in sequence.

[0045] In the present invention, the photovoltaic device can be a formal single-junction perovskite solar cell, an inverted single-junction perovskite solar cell, a formal tandem perovskite solar cell or an inverted tandem perovskite solar cell.

[0046] In the present invention, the formal single-junction perovskite solar cell may include a transparent conductive substrate, an electron transport layer, a perovskite film, a hole transport layer and a back electrode in sequence. In the present invention, the inverted single-junction perovskite solar cell may include a transparent conductive substrate, a hole transport layer, a perovskite film, an electron transport layer and a back electrode in sequence.

[0047] In the present invention, the formal stacked perovskite solar cell may include a bottom electrode, a bottom cell, a tunneling layer, a formal perovskite top cell and a top electrode in sequence, and the positive electrode top cell may include an electron transport layer, a perovskite film and a hole transport layer in sequence.

[0048] In the present invention, the inverted stacked perovskite solar cell may include a bottom electrode, a bottom cell, a tunneling layer, an inverted perovskite top cell and a top electrode in sequence, and the inverted top cell may include a hole transport layer, a perovskite film and an electron transport layer in sequence.

[0049] In the present invention, the transparent conductive substrate may be an indium tin oxide (ITO) substrate, a fluorine-doped tin oxide (FTO) substrate or an indium zinc oxide (IZO) substrate.

[0050] In the present invention, the hole transport layer can be an inorganic transport material and / or an organic p-type semiconductor material. In the present invention, the inorganic transport material can be one or more selected from nickel oxide (NiO), cuprous oxide (Cu2O), molybdenum oxide (MoO3), copper iodide (CuI) and redox graphene. In the present invention, the organic p-type semiconductor material can be one or more selected from poly [bis (4-phenyl) (2,4,6-trimethylphenyl) amine] (PTAA, poly (triaryl amine)), 2,2',7,7'-tetrakis [N,N-di (4-methoxyphenyl) amino] -9,9'-spirobifluorene (Spiro-OMeTAD), poly 3,4-ethylenedioxythiophene: polystyrene sulfonate (PEDOT:PSS), poly [bis (4-phenyl) (4-butylphenyl) amine] (Ploy-TPD), [2- (9H-carbazole-9-yl) ethyl] phosphonic acid and [2- (3,6-dimethoxy-9H-carbazole-9-yl) ethyl] phosphonic acid (MeO-2PACz).

[0051] In the present invention, the thickness of the hole transport layer can be 0.5-50 nm, for example, 0.5 mm, 1 mm, 5 mm, 10 mm, 20 mm, 30 mm, 40 mm, 50 mm.

[0052] In the present invention, the electron transport layer may be an n-type semiconductor material. In the present invention, the n-type semiconductor material may be one or more selected from titanium oxide (TiO2), tin oxide (SnO2), zinc oxide (ZnO), fullerene (C60), graphene, and fullerene derivatives (PCBM). In the present invention, the thickness of the electron transport layer may be 2-200nm, for example, 2mm, 5mm, 10mm, 20mm, 50mm, 150mm, 200mm.

[0053] In the present invention, the back electrode may be one or more selected from the group consisting of gold, palladium, silver, titanium, chromium, nickel, aluminum, copper, indium tin oxide (ITO) and indium zinc oxide (IZO).

[0054] In the present invention, the top electrode may include a transparent conductive layer; preferably, the top electrode may also include a gate line electrode; more preferably, the top electrode may also include an anti-reflection layer.

[0055] In the present invention, the tunneling layer can be one or more selected from indium tin oxide (ITO), indium zinc oxide (IZO), cerium-doped indium oxide (ICO), tungsten-doped indium oxide (IWO), aluminum-doped zinc oxide (AZO), barium zirconate (BZO), fluorine-doped tin oxide (FTO) and indium oxide (IO).

[0056] In the present invention, the bottom cell may be a crystalline silicon bottom cell, a perovskite bottom cell, a copper indium gallium selenide bottom cell, a cadmium telluride bottom cell or an organic bottom cell. In the present invention, the bottom electrode may include a transparent conductive layer; preferably, the bottom electrode may also include a gate electrode.

[0057] In the present invention, the transparent conductive layer can be selected from one or more of indium tin oxide (ITO), indium zinc oxide (IZO), cerium-doped indium oxide (ICO), tungsten-doped indium oxide (IWO), aluminum-doped zinc oxide (AZO), barium zirconate (BZO), fluorine-doped tin oxide (FTO) and indium oxide (IO).

[0058] In the present invention, the gate line electrode may be one or more selected from silver, copper, aluminum or alloys containing such metal elements.

[0059] The method for preparing a formal single-junction perovskite solar cell of the present invention may include the following steps:

[0060] (1) depositing an electron transport layer on the surface of a transparent conductive substrate;

[0061] (2) depositing a perovskite film on the surface of the electron transport layer;

[0062] (3) depositing a hole transport layer on the surface of the perovskite film;

[0063] (4) A back electrode is deposited on the surface of the hole transport layer to obtain a formal single-junction perovskite solar cell.

[0064] The method for preparing an inverted single-junction perovskite solar cell of the present invention may include the following steps:

[0065] (1) depositing a hole transport layer on the surface of a transparent conductive substrate;

[0066] (2) depositing a perovskite film on the surface of the hole transport layer;

[0067] (3) depositing an electron transport layer on the surface of the perovskite film;

[0068] (4) A back electrode is deposited on the surface of the electron transport layer to obtain an inverted single-junction perovskite solar cell.

[0069] The method for preparing a formal tandem perovskite solar cell of the present invention may include the following steps:

[0070] (1) depositing a bottom electrode and a tunneling layer on both sides of the bottom cell;

[0071] (2) depositing an electron transport layer on the surface of the tunneling layer;

[0072] (3) depositing a perovskite film on the surface of the electron transport layer;

[0073] (4) depositing a hole transport layer on the surface of the perovskite film;

[0074] (5) Depositing a top electrode on the surface of the hole transport layer to obtain a formal laminated perovskite solar cell.

[0075] The method for preparing an inverted stacked perovskite solar cell of the present invention may include the following steps:

[0076] (1) depositing a bottom electrode and a tunneling layer on both sides of the bottom cell;

[0077] (2) depositing a hole transport layer on the surface of the tunneling layer;

[0078] (3) depositing a perovskite film on the surface of the hole transport layer;

[0079] (4) depositing an electron transport layer on the surface of the perovskite film;

[0080] (5) A top electrode is deposited on the surface of the electron transport layer to obtain an inverted stacked perovskite solar cell.

[0081] In the present invention, the electron transport layer can be deposited by electron beam evaporation, thermal evaporation, magnetron sputtering, atomic layer deposition, spin coating or doctor blade coating.

[0082] In the present invention, the hole transport layer may be deposited by spin coating.

[0083] Compared with the prior art, the present invention has the following beneficial effects: the present invention can significantly reduce the cost of purchasing ultra-dry raw materials; the perovskite precursor solution with low water content prepared by adding the dehydrated perovskite powder into a solvent can significantly improve the device performance of the perovskite solar cell.

[0084] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0085] Comparative Example 1

[0086] In this embodiment, the structure is prepared as Figure 1 The specific preparation process of the perovskite solar cell shown in (a) is as follows:

[0087] 1. Preparation of hole transport layer: [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) was dissolved in ethanol to prepare a MeO-2PACz solution with a concentration of 1 mmol / mL. 130 μL of MeO-2PACz solution was added dropwise on a cleaned ITO glass (transparent conductive substrate) with a size of 2.5 cm*2.5 cm, and then spin-coated at a speed of 4000 rpm for 15 seconds. After the spin coating, it was transferred to a hot plate at 100°C for annealing for 10 minutes, and then removed to obtain a hole transport layer with a thickness of 2 nm.

[0088] 2. Preparation of perovskite film: 19.5 mg of cesium iodide (CsI), 232.2 mg of iodomethane (FAI), 11.9 mg of iodomethane (MAI), and 691.5 mg of lead iodide (PbI2) were dissolved in a mixed solvent of 800 μL of DMF and 200 μL of DMSO, and the mixed solution was filtered through a 250 μm oil filter to obtain a perovskite precursor solution containing 1.5 mol / L of FA 0.9 MA 0.05 Cs 0.05 PbI3(FAMACs); a perovskite thin film layer was prepared by spin coating, and the specific operation was as follows: a perovskite precursor solution was placed in a glove box for spin coating, 100 μL of the perovskite precursor solution was first dripped on the surface of the hole transport layer, and the spin coating was performed according to a process of 2000 rpm for 10 s and 6000 rpm for 30 s for a total of 40 s, 300 μL of anisole solution (anti-solvent) was taken up with a 1 μL pipette tip, and anisole solution was dripped when the perovskite precursor solution was spin coated for 30 s, and the film was removed from the spin coater after the spin coating stopped, and heated on a heating plate at 100°C for 10 min to obtain a perovskite film, and the thickness of the perovskite film was 600 nm;

[0089] 3. Preparation of electron transport layer: Fullerene (C60) is deposited on the surface of the perovskite film by thermal evaporation to obtain a fullerene layer with a thickness of 25 nm; tin dioxide (SnO2) is deposited on the fullerene surface by atomic layer deposition to obtain a tin dioxide layer with a thickness of 20 nm. The fullerene layer and the tin dioxide layer together constitute the electron transport layer. During the thermal evaporation process, the temperature of the evaporation source is 450°C and the evaporation rate is 0.1 A / s;

[0090] 4. Preparation of back electrode: The thermal evaporation method is used to deposit metallic copper on the surface of the electron transport layer to obtain a back electrode and a perovskite solar cell at the same time. The thickness of the back electrode is 200 nm.

[0091] Comparative Example 2

[0092] In this embodiment, the structure is prepared as Figure 1The specific preparation process of the perovskite solar cell shown in (b) is as follows:

[0093] 1. Preparation of bottom cell: Using plasma enhanced chemical vapor deposition (PECVD) process, intrinsic amorphous silicon layers (a-Si(i)) are deposited on both sides of the intrinsic silicon layer (c-Si(n)) at 200°C to obtain a passivation layer, and then n-type microcrystalline silicon layers and p-type microcrystalline silicon layers are deposited on both sides of the passivation layer to obtain an electron transport layer (nc-Si(p)) and a hole transport layer (nc-Si(p)), respectively, to obtain a bottom cell. The thickness of the bottom cell is 300μm.

[0094] 2. Preparation of bottom electrode and tunneling layer: ITO is deposited on the surface of p-type microcrystalline silicon layer by physical vapor deposition to obtain a transparent electrode layer with a thickness of 80nm, silver is printed on the surface of transparent electrode layer by printing method to obtain a gate electrode with a height of 20μm and a width of 30μm, and the transparent electrode layer and the gate electrode constitute the bottom electrode; ITO is deposited on the surface of n-type microcrystalline silicon layer by sputtering method to obtain a tunneling layer with a thickness of 20nm;

[0095] 3. Preparation of hole transport layer: [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz) was dissolved in ethanol to prepare a MeO-2PACZ solution with a concentration of 1 mmol / mL. 130 μL of MeO-2PACz solution was added dropwise to the surface of the tunneling layer ITO, and then spin-coated at a speed of 4000 rpm for 15 seconds. After the spin coating, it was transferred to a hot plate at 100°C for annealing for 10 minutes, and then removed to obtain a hole transport layer with a thickness of 2 nm.

[0096] 4. Preparation of perovskite film: 88.3 mg of cesium iodide (CsI), 233.9 mg of iodomethane (FAI), 187.2 mg of lead bromide (PbBr2), and 548.6 mg of lead iodide (PbI2) were dissolved in a mixed solvent of 800 μL DMF and 200 μL DMSO, and the mixed solution was filtered using a 250 μm oil filter to obtain a perovskite precursor solution. The perovskite precursor solution contained 1.7 mol / L of FAI. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3; Prepare the perovskite film by scraping; The specific operation is as follows: Take 10μL of perovskite precursor droplet on the scraper head, the scraper moves at a speed of 5mm / s, the scraper height is 100μm, and after scraping, use N2 air knife to blow, the blowing pressure is 0.5Mpa, the moving speed is 20mm / s, and after blowing, the perovskite film is annealed on a heating plate at 100°C for 10min to obtain a perovskite film, and the thickness of the perovskite film is 1500nm;

[0097] 5. Preparation of electron transport layer: Fullerene (C60) is deposited on the surface of the perovskite film by thermal evaporation to obtain a fullerene layer with a thickness of 12 nm; tin dioxide (SnO2) is deposited on the fullerene surface by atomic layer deposition to obtain a tin dioxide layer with a thickness of 20 nm. The fullerene layer and the tin dioxide layer together constitute the electron transport layer. During the thermal evaporation process, the temperature of the evaporation source is 450°C and the evaporation rate is 0.1 A / s;

[0098] 6. Preparation of the top electrode: IZO is deposited on the surface of the electron transport layer by physical vapor deposition (PVD) to obtain a transparent conductive layer with a thickness of 70 nm; MgF2 is deposited on the surface of the transparent conductive layer by thermal evaporation to obtain an anti-reflection layer with a thickness of 120 nm; finally, silver is deposited on the surface of the anti-reflection layer by thermal evaporation to obtain a 800 nm gate electrode. The transparent conductive layer, anti-reflection layer and gate electrode together constitute the top electrode, and a perovskite solar cell is obtained at the same time.

[0099] Example 1

[0100] The difference between this embodiment and comparative example 1 is that the preparation process of the perovskite precursor solution in step (2) is different: in this embodiment, 19.5 mg of cesium iodide (CsI), 232.2 mg of iodomethane (FAI), 11.9 mg of iodomethane (MAI), and 691.5 mg of lead iodide (PbI2) are placed in a mortar and ground in a N2 glove box for 2 h, and then heated at 60°C and 1×10 -3 Pa vacuum drying for 6 hours to obtain the dry perovskite structure material raw material FA 0.9 MA 0.05 Cs 0.05 PbI3 powder, the dried perovskite structure material raw material was dissolved in a mixed solvent of 800μL DMF and 200μL DMSO, and the mixed solution was filtered using a 250μm oil filter to obtain a perovskite precursor solution, which contained 1.5mol / L FA 0.9 MA 0.05 Cs 0.05 PbI3(FAMACs).

[0101] Example 2

[0102] The difference between this embodiment and comparative example 2 is that the preparation process of the perovskite precursor solution in step (4) is different: in this embodiment, 88.3 mg of cesium iodide (CsI), 233.9 mg of iodomethane (FAI), 187.2 mg of lead bromide (PbBr2), and 548.6 mg of lead iodide (PbI2) are placed in a mortar and ground in a N2 glove box for 2 h, then heated at 60°C, 1*10 -3The dried perovskite material FA was obtained by vacuum drying at 400 Pa for 6 h. 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3 powder, the dried perovskite structure material raw material was dissolved in a mixed solvent of 800μL DMF and 200μL DMSO, and the mixed solution was filtered using a 250μm oil filter to obtain a perovskite precursor solution, which contained 1.7mol / L FA 0.8 Cs 0.2 Pb(I 0.8 Br 0.2 )3(FAMACs).

[0103] Test Case

[0104] Device performance test of perovskite solar cells: Under the AM 1.5G standard solar spectrum, a solar simulator was used to set the voltage range to sweep from 2.1V to -0.3V, and the current output of the perovskite solar cells prepared in Example 1-2 and Comparative Example 1-2 at different voltages was tested, and the corresponding current-voltage (IV) characteristic curves were plotted, where the cell surface area was 1.21cm 2 , the incident light power (Pin) is 100mW / cm 2 The open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the perovskite solar cells prepared in Example 1-2 and Comparative Example 1-2 were obtained according to the characteristic curves.

[0105] (1) Open circuit voltage (Voc): The voltage value corresponding to when the current is equal to zero.

[0106] (2) Short-circuit current density (Jsc): The current value when the voltage is zero is the short-circuit current (Isc), and the current per unit battery surface area is the short-circuit current density.

[0107] (3) Fill factor (FF): The ratio of the maximum output power (Pmax) of the battery to the product of the open circuit voltage and the short circuit current. The calculation formula is (Pmax / Voc*Isc), where the maximum power point is the point where the battery output power reaches its maximum value.

[0108] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)*100%.

[0109] The test results of the open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of the perovskite solar cells prepared in Example 1-2 and Comparative Example 1-2 are shown in Table 1.

[0110] Table 1: Open circuit voltage, short circuit current density, fill factor and photoelectric conversion efficiency of perovskite solar cells prepared in Examples 1-2 and Comparative Examples 1-2

[0111] <![CDATA[V OC (V)]]> <![CDATA[J SC (mA / cm 2 )]]> FF(%) PCE(%) Example 1 1.15 25.4 82.1 24.0 Example 2 2.01 20.3 83.1 33.9 Comparative Example 1 1.11 25.0 81.8 22.7 Comparative Example 2 1.98 20.2 82.1 32.8

Claims

1. A method for preparing a perovskite precursor solution, characterized in that: The method comprises: grinding a raw material of a perovskite structure material in an inert gas, and then drying to obtain a dried raw material of the perovskite structure material, and dissolving the dried raw material of the perovskite structure material in a solvent to obtain a perovskite precursor solution.

2. The method according to claim 1, characterized in that The method has one or more of the following features: The raw materials of the perovskite structure material are AX and BX2, A is a monovalent cation, including but not limited to one or more of cesium ion, rubidium ion, methylamine ion, dimethylamine ion, formamidine ion and guanidine ion; B is a divalent cation, including but not limited to one or more of lead ion, copper ion, zinc ion, gallium ion, tin ion and calcium ion; X is a monovalent anion, including but not limited to one or more of iodide ion, bromide ion, chloride ion, fluoride ion, thiocyanate ion, tetrafluoroborate ion and hexafluorophosphate ion; The inert gas is nitrogen or argon; Grinding time is 1-24h; Drying is carried out under vacuum conditions with a vacuum degree of less than 10 -3 Pa; Drying temperature is -100-60℃; Drying time is 6-48h.

3. The method according to claim 1, characterized in that In the perovskite precursor solution, the solvent is selected from one or more of ethanol, isopropanol, methanol, butanol, pentanol, N,N-dimethylformamide, dimethyl sulfoxide, 1,3-dimethyl-3,4,5,6-tetrahydro-2-pyrimidinone, acetonitrile, diphenyl sulfoxide and dimethoxyethanol.

4. The method according to claim 2, characterized in that In the perovskite precursor solution, the concentration of B-site ions is 0.1-2.4 mol / L.

5. A perovskite precursor solution prepared by the method according to any one of claims 1 to 4.

6. A method for preparing a perovskite film, characterized in that: The method comprises: coating the perovskite precursor solution according to claim 5, and then annealing to obtain a perovskite film.

7. The method according to claim 6, characterized in that The method has one or more of the following features: The coating method is spin coating, blade coating, spray pyrolysis, inkjet printing or slot coating; Annealing temperature is 90-150°C; The annealing time is 10-60min.

8. A perovskite film prepared by the method according to claim 6 or 7.

9. The perovskite film according to claim 8, characterized in that The perovskite film contains a perovskite structure material, the chemical formula of the perovskite structure material is ABX3, A is a monovalent cation, including but not limited to one or more of cesium ion, rubidium ion, methylamine ion, dimethylamine ion, formamidine ion and guanidine ion; B is a divalent cation, including but not limited to one or more of lead ion, copper ion, zinc ion, gallium ion, tin ion and calcium ion; X is a monovalent anion, including but not limited to one or more of iodide ion, bromide ion, chloride ion, fluoride ion, thiocyanate ion, tetrafluoroborate ion and hexafluorophosphate ion.

10. A photovoltaic device, characterized in that: The photovoltaic device comprises the perovskite thin film according to claim 8 or 9.

Citation Information

Cited By

  • Chiral perovskite thin film, preparation method and circular polarization light emitting diode device

    CN120865892A